(untitled) (Medical Forum Monthly, 2024)
Introduction: Osteoporosis is a progressive systemic disease of the bone causing significant reduction in bone mineral density and microarchitecture of bone tissue .All women experience slow bone loss with age . In Pakistan accelerated bone loss at menopause in women is about 75.3% increasing upto 97%with age thus making osteoporosis a major health problem.At the time of menopause, serum automated β-Crosslaps increases by 86% a pattern consistent with accelerated bone loss within the first few years following menopause .we therefore hypothesized that estimation and comparsion β-Crosslaps levels in Premenopausal and Postmenopausal women may be use as a diagnostic and screening marker for prevention of postmenopausal osteoporosis. Study Design: A cross sectional comparative study. Place and Duration of Study: This study was conducted in department of Physiology, BMSI in collaboration with Karachi gymkhana through a medical campaign in September 2011 Materials and Methods: A total of 94 subjects (premenopausal and postmenopausal) were included in this study that was performed in the urban area of Karachi city in 2011. Data was collected from all subjects through a questionnaire including questions regarding their age, menstrual history, menopausal and medical history. Blood samples from all these subjects were collected for the determination of bone turnover marker beta crosslaps. Bone mineral density (BMD) of the heel bone was done by single x-ray absorptiometry. Results: The results of our study showed that the levels of serum β-Crosslaps in postmenopausal women were significantly higher as compared to premenopausal women p<0.01.There was a significant rise in the β-Crosslaps levels with the increasing age among the postmenopausal women p<0.01.BMD (bone mineral density) value have negative correlation the beta crosslaps levels p <0.01 i.e with the increasing age there was decrease in BMD value and increase in β-crosslaps values. Conclusion: Serum β-crosslaps levels in postmenopausal women can provide valuable information regarding the decreasing bone density and hence may be considered a cost effective diagnostic as well as screening marker for the prevention of postmenopausal osteoporosis.